Clinical Characteristics and Manifestation of Herpes Esophagitis: One Single-center Experience in Taiwan. Issue 14 (April 2016) - Wang, Hung-Wei; Kuo, Chia-Jung; Lin, Wey-Ran; Hsu, Chen-Ming; Ho, Yu-Pin; Lin, Chun-Jung; Su, Ming-Yao; Chiu, Cheng-Tang; Chen, Kuang-Hua
Abstract : Abstract: We aimed to investigate the clinical characteristics of patients with herpes esophagitis (HE) based on endoscopic typing. Herpes simplex virus infection in the gastrointestinal tract primarily affects the esophagus. However, little is known about the presentation, endoscopic findings, and outcomes of HE. From 2003 to 2013, 47 patients with HE were identified histologically from among 1843 patients with esophageal ulcers. Personal data, underlying disease, esophagogastroduodenoscopy indication, endoscopic characteristics, pathological findings, laboratory data, and outcomes were collected. Endoscopic findings were classified into 3 types based on gross appearance and were correlated with clinical presentation. The mean age of patients was 62.04 ± 14.76 years, and most patients were men (39/47, 83%). The most common symptoms were odynophagia/dysphagia (20/47, 42.6%). Whereas 25 patients (53.2%) were diagnosed with malignancy, it was related to human immunodeficiency virus in only 1 patient (2.1%). HE was classified into 3 types based on endoscopic images: type I (n = 19), type II (n = 10), and type III (n = 18). The majority of patients with HE type III had sepsis (72%) and obvious leukocytosis than the other 2 types ( P  = 0.03). The overall mortality rate was 6.4% (3/47), and most of the patients who died (66.7% [2/3]) belonged to the endoscopic classification type III group. Clinical parameters were analyzed for the risk of poor outcome. Postchemotherapy and/or radiotherapy were associated with 30-day mortality after appearance of HE ( P  < 0.05). Herpes esophagitis primarily affects men and patients with malignancy or sepsis. However, the disease is usually self-limiting, and HE-related mortality is low. Relationship between severity of endoscopic findings and patients' outcome remains questionable. Further prospective study is needed.